Measurements of ground temperatures in Cyprus for ground thermal applications - Pouloupatis, Panayiotis; Florides, Georgios A.; Tassou, Savvas A. (My University, 2011)
The knowledge of the thermal behaviour of the ground and the factors affecting it are important for many construction projects and for using the ground as heat storage or a heat exchange media. Not enough information exists regarding the thermal behaviour of the ground in Cyprus and this is one of the main interests of this study. The ground temperature distribution was recorded for the period between May 2006 and May 2007, at the Athalassa region in Nicosia. For this purpose a borehole was drilled and a U-tube heat exchanger made of 32 mm external diameter polyethylene pipe and thermocouples were placed up to the depth of 50 m. All data were recorded using an Omega OMB-DAQ 55/65 USB data acquisition module for a typical day each month at 15 min intervals. The surface zone in the area, reaches the depth of 0.5 m while the shallow zone extends up to 7 m. Below the 7 m depth the temperature remains almost unchanged at 22.6 °C and close to the mean annual ambient air temperature of 19.5 °C. Ground temperatures up to the depth of 7 m and 7.7 m were also recorded at the Ariel and Ayia Phyla locations in Limassol, respectively. The two boreholes were drilled to study and compare the thermal behaviour of the ground in other lowland places of the Island of Cyprus as well. The comparison of the data collected showed almost no differences between the three data collection points in the ground temperature distribution regardless of the differences in the composition of the ground
Keywords: Ground temperature; Ground thermal behaviour; Measurements